Sequestering survival: sponge-like proteins in phage evasion of bacterial immune defenses - Wang, Lan; Zheng, Ruoqi; Zhang, Leiliang (Frontiers in Immunology, 2025)
By executing abortive infection, bacterial immune defense systems recognize phage components and initiate the production of various second messengers that target specific downstream effectors responsible for nucleic acid degradation, membrane destruction, or metabolite depletion. Notably, the sponge-like proteins encoded by phages, such as Tad1, Tad2, and Acb2, can inhibit abortive infection by sequestering, rather than degrading, these bacterial second messengers. This interference disrupts the activation of the effectors involved in the immune response. Most significantly, sponge-like proteins can simultaneously encapsulate diverse signals, effectively preventing the cell suicide mechanisms triggered by different bacterial immune systems, such as the cyclic nucleotide-based antiphage signaling system (CBASS) and Thoeris. The discovery of these sponge-like proteins reveals a remarkable strategy for suppressing innate immunity, ensuring viral replication and propagation. This greatly enhances our understanding of the ongoing arms race between hosts and viruses.